Pengembangan booklet digital berbantuan HTML 5 pada materi keragaman budaya Indonesia siswa kelas XI SMA - Hasna Indriani; Fatiya Rosyida; Djoko Soelistijo; Yusuf Suharto (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
The need for teaching materials in supporting learning that is adapted to student learning conditions is very necessary. Based on the phenomena in the field, it is known that there is a need for teaching materials that can help students understand the material and support online learning. The purpose of this research is to produce a supplement product for teaching materials in the form of digital booklets assisted by HTML 5 technology to support geography learning, especially material on cultural diversity in Indonesia. The research uses the ADD development model which consists of the Analyze, Design and Development stages. The research subjects were material expert validators, teaching materials and linguistics as well as teachers and students of class XII SMA Negeri 5 Malang. The results obtained from the percentage of teaching material validation are 96 percent in the "Very Valid" category and material validation is 77 percent, and language validation is 80% in the "Valid" category. While the results of the response to the feasibility of digital booklets for research subjects, namely the teacher obtained a total percentage of between 74 percent in the "Eligible" category and 90 percent for students in the "Very Eligible" category. Based on the results of the research obtained and analyzed, it can be concluded that the digital booklet that has been developed is valid and suitable to be used as a supplement to teach materials in geography learning the subject matter of cultural diversity in Indonesia. Kebutuhan bahan ajar dalam penunjang pembelajaran yang disesuaikan dengan kondisi belajar siswa sangat diperlukan. Berdasarkan fenomena di lapangan diketahui bahwa adanya kebutuhan bahan ajar yang dapat membantu siswa memahami materi dan mendukung pembelajaran online. Tujuan penelitian ini adalah menghasilkan produk bahan ajar berupa booklet digital berbantuan teknologi HTML 5 untuk menunjang pembelajaran geografi khususnya materi keragaman budaya di Indonesia. Penelitian menggunakan model pengembangan ADD yang terdiri dari tahap Analyze (analisis), Design (perancangan) dan Development (Pengembangan). Subjek penelitian adalah validator ahli materi, desain dan kebahasaan serta guru dan siswa kelas XII SMA Negeri 5 Malang. yang diperoleh dari persentase validasi bahan ajar sebesar 96 persen dengan kategori “Sangat Valid” serta validasi materi sebesar 77 persen, dan validasi bahasa sebesar 80 persen dengan kategori “Valid”. Sedangkan pada hasil respon kelayakan booklet digital terhadap subjek penelitian yaitu guru memperoleh total persentase antara 74 persen dengan kategori “Layak” dan terhadap siswa sebesar 90 persen dengan kategori “Sangat Layak”. Berdasarkan hasil penelitian yang diperoleh dan telah dianalisis dapat disimpulkan bahwa booklet digital yang telah dikembangkan valid dan layak digunakan sebagai bahan ajar dalam pembelajaran geografi pokok materi keragaman budaya di Indonesia.